Effectiveness of myopia control interventions - Lanca, Carla (2023)
Publisher Copyright: Copyright © 2023 Lanca, Pang and Grzybowski. Errata publicada em: Lanca C, Pang CP, Grzybowski A. Corrigendum: Eectiveness of myopia control interventions: a systematic review of 12 randomized control trials published between 2019 and 2021. Front. Public Health. 2024;12:1460156. doi: 10.3389/fpubh.2024.146015